Mechanical and Thermal Performance of Cement Mortar Incorporating Super Absorbent Polymer (SAP) - Rahman, Md Mahfuzur; Jyoti, Laila Tul Zannat; Paul, Snahashish; Ishmam, Al-; Hossain, Md Akhtar (Civil Engineering Journal, 2020)
Super Absorbent Polymer (SAP) is a favorable admixture which can influence various properties of cementitious materials. It mainly improves the water retaining properties of cement-based construction materials. In this paper, an experimental program was carried out to determine the mechanical and thermal performance of cement plaster containing SAP. Firstly, the absorption capacity of SAP was determined in different loading conditions and chloride solutions. Thereafter, the optimum dosage of SAP for cement plaster was also determined from five different proportions of SAP (0.05, 0.1, 0.3, 0.5 and 1% of cement mass) based on the compressive strength test results. The mortar incorporating 0.05% SAP of cement mass was selected as the optimum dosage, which yielded the highest compressive strength. Two slabs of 1×1×25 mm with 0.05% SAP and two slabs of 1×1×25 mm without SAP were cast to determine the thermal performance of the cement mortar with and without SAP. For this purpose, a wooden chamber of 2×1×1 m was constructed and the slab was placed in the middle of this chamber to carry out the thermal performance test of cement mortar. The slabs with 0.05% SAP showed promising results for acting as a thermal barrier in buildings compared to slabs without SAP. Doi: 10.28991/cej-2020-03091614 Full Text: PDF